1972
DOI: 10.1002/ar.1091740303
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo incorporation of choline‐3H, leucine‐3H and galactose‐3H in alveolar type II pneumocytes in relation to surfactant synthesis. A quantitative radioautographic study in mouse by electron microscopy

Abstract: A quantitative time study of the incorporation of choline-SH, le~cine-~H and gala~tose-~H in lung epithelial cells, was undertaken in vivo with electron microscopic autoradiography. Type I1 pneumocytes were selectively labeled with ~holine-~H, a specific precursor of phosphatidylcholine, which is the main component of pulmonary surfactant. Choline was initially localized in endoplasmic reticulum, then was rapidly transferred through the Golgi complex and stored in lamellar bodies. Previously undescribed small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
0
4

Year Published

1974
1974
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(105 citation statements)
references
References 61 publications
3
98
0
4
Order By: Relevance
“…as also indicatcrl by other investigators (10,12,16,19,25,32). These bioche~nical studies also confirmed tlie electron microscopic autoradiography findings that I'C \vas initially synthesi/ed in cndoplasmic ~e t i c u l u m (8). T h e rnitochondri;~ may hiivc enzymes required for the synthesis of membrane pliosl~liolipids (25).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…as also indicatcrl by other investigators (10,12,16,19,25,32). These bioche~nical studies also confirmed tlie electron microscopic autoradiography findings that I'C \vas initially synthesi/ed in cndoplasmic ~e t i c u l u m (8). T h e rnitochondri;~ may hiivc enzymes required for the synthesis of membrane pliosl~liolipids (25).…”
Section: Discussionsupporting
confidence: 80%
“…12, 17, 18, 20, 36) have suygcstccl that the PC-IysoPC cyclc p:rth\v;~y may he import:rnt in the rcmocleling of tlic lung surfactant, the mcc1i;rnism is not cle;~r. Chcvalicr and Collctt (8) obscrvcd that PC w:ls initially syntllcsizcd in crldoplasrnic rcticulunl ;111d then transferretl to Ii~rncllar bodies through Golgi complex. Rooncy c.1 nl.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in rats (19), lambs (I), and rabbits (30) suggest that surfactant replacement therapy may be applicable to the human; however, the basic difference between lung surfactant metabolism between perinatal and adult mammals have been used to study subcellular synthesis, storage, and secretion of phosphatidylcholine in fetal (26), premature (23), term newborn (14,24), and adult rabbits (21,25). These studies are consistent with the anatomic descriptions of the subcellular metabolism of surfactant (7,8), and they have shown striking differences between perinatal and adult rabbits in the kinetics of labeled phosphatidylcholine secretion to the alveolar space.…”
Section: Speculationsupporting
confidence: 85%
“…Autoradiographic studies of murine type II alveolar cells of mouse lungs showed that although phospholipids labeled with [ 3 H]choline are delivered directly from the Golgi to the MLB, proteins metabolically labeled with [ 3 H]leucine are visualized within multivesicular bodies before delivery to MLBs (Chevalier and Collet, 1972). Surfactant proteins A, B, and C are delivered via multivesicular bodies to MLBs, and multivesicular bodies are proposed as the site of processing of surfactant precursor to mature forms; both multivesicular bodies and MLBs express the lysosomal marker CD63 and are therefore part of the lysosomal pathway (Voorhut et al, 1992(Voorhut et al, , 1993.…”
Section: Introductionmentioning
confidence: 99%